Misalignment between national resource inventories and policy actions drives unevenness in the energy transition - John R. Owen; Deanna Kemp; Waleria Schuele; Julia Loginova (Communications Earth & Environment, 2023)
Abstract To make projections about the future supply of minerals for the energy transition and set climate targets, it is important to understand inventories of mineral resources as well as national extraction policies. Here, we combine data on mining properties and policies between 2020 and 2023 for 18 countries with substantial resources of energy transition minerals to understand the alignment between the resource inventories and policy actions to make these mineral resources available to market. We find the distribution and near-term production-readiness of energy transition minerals varies across countries. The results show extraction policies align with demand for energy-transition minerals more strongly for countries in the OECD (Organization for Economic Cooperation and Development) compared with their non-OECD counterparts. We suggest these differences between countries could lead to global-scale delays in mitigating climate change and an uneven energy transition structured around national resource endowment, wealth, and inequality.